儒家“誠”基礎上的器官家庭捐獻: Family Priority and Consent in Organ Donation: An Argument Based on the Confucian Idea of Sincerity - CAI, Yu (International Journal of Chinese & Comparative Philosophy of Medicine, 2018)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文首先探討了儒家的“誠”與作為人之本性的“仁”之間的關係，指出“誠”是“仁”的前提與基礎。筆者認為“誠”賦予“仁”三個基本特徵：“真摯性”、“無外在目的性”和“客觀性”。這三個特徵都與儒家家庭和家庭成員間的“親親之愛”緊密聯繫。其後，本文提出儒家排斥“鄉願”式的器官捐獻。同時，文章指出，由於“誠”的要求，儒家認為對家庭成員的“親親之愛”應該是對非家庭成員的仁愛的前提、基礎和不可或缺的必要條件。因而，個人捐獻原則是與“誠”的價值觀存在一定的矛盾，而家庭捐獻原則才是符合儒家倫理的。最後，本文對人體器官的家庭捐獻原則進行了制度設計。 Organ donation is the gift of an organ to help someone who needs a transplant to survive. Yet with limited organs available, the following question arises. Who should be given priority in terms of donation procedures—the individual who has personally committed to offer his/her organs to anyone in need, or the legal next of kin, i.e., family members? This essay approaches this question with reference to the Confucian ethics of sincerity (cheng), which is viewed as a precondition for the ethics of humanness (ren), arguing that family members should be given priority in decisions on organ donation. The author recommends that a policy of family consent for organ donation be implemented, as such a policy would reflect the significant role that family should play in making decisions on critical issues such as organ donation. The essay concludes that rather than emphasizing the right of individuals to decide what will happen after they die, a policy of family involvement would encourage more people to become donors and avoid conflict in cases of disagreement between donors and family members. DOWNLOAD HISTORY | This article has been downloaded 75 times in Digital Commons before migrating into this platform.